Synthesis of biquad filters using two VD-DIBAs with independent control of quality factor and natural frequency - Jaikla, Winai; Siripongdee, Surapong; Khateb, Fabian; Sotner, Roman; Silapan, Phamorn; Suwanjan, Peerawut; Chaichana, Amornchai (My University, 2021)
This contribution presents the procedure to synthesis the voltage-mode active biquad filters using the active elements, voltage differencing differential input buffered amplifier (VD-DIBA). Two filtering categories, single input four output (SIFO) configuration and three input three output (TITO) configuration are proposed. Both proposed filters consist of two VD-DIBAs, two grounded capacitors and two resistors. All input voltage nodes for both biquad filters exhibit high impedance. The proposed SIFO biquad filter simultaneously provide four filtering responses, low pass (LP), band pass (BP), high pass (HP) and band reject (BR) functions, while the proposed TITO filter provides five filtering responses (including all pass (AP) function). The natural frequency (ω0) is linearly and electronically tuned without affecting the quality factor (Q). Also, the Q adjusting can be done without affecting the ω0. By modifying the proposed TITO biquad filter, the current controlled sinusoidal oscillator is achieved. The frequency of the generated sinewave is linearly tuned without affecting the condition of oscillation. The performances of the proposed circuits are simulated by Cadence software and the Spectre simulator of the Analog Design Environment using CMOS VD-DIBA in 0.18 μm TSMC CMOS technology and laboratory experiment using VD-DIBA constructed from commercially available ICs.
Keywords: Biquad filter; Electronic controllability; Sinusoidal oscillator; VD-DIBA